Effect of Non-genetic Factors on Udder Biometry of Indigenous Cattle of Arunachal Pradesh, India - Kakki, Marpi; Zaman, Galib Uz; Akhtar, Farzin; Das, Arpana; Das, Bula; Phookan, Arundhati (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
The study was undertaken to estimate the effect non-genetic factors on the udder biometry of indigenous cattle of Arunachal Pradesh. A total of 158 indigenous cows were utilized to study the effect of location and lactation order on udder characteristics. Length of udder (LU), width of udder (WU), depth of udder (DU), teat length (TeL) and teat diameter (TeD) were included in the present investigation. The data on udder measurement were classified according to location and lactation order of the animal. The means for LU, WU, DU, TeL and TeD were 30.940 ± 0.105, 21.506 ± 0.069, 9.923 ± 0.037, 4.459 ± 0.024, and 2.762 ± 0.025 cm respectively. Location and lactation order had significant effect on all the udder measurement traits. Existence of significant effect of this non-genetic factor indicates that these factors should be taken care of while estimating the genetic parameters for udder characteristics of indigenous cattle of Arunachal Pradesh.